2018
DOI: 10.1016/j.molcel.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Spt6 Is Required for the Fidelity of Promoter Selection

Abstract: SUMMARY Spt6 is a conserved factor that controls transcription and chromatin structure across the genome. Although Spt6 is viewed as an elongation factor, spt6 mutations in Saccharomyces cerevisiae allow elevated levels of transcripts from within coding regions, suggesting that Spt6 also controls initiation. To address the requirements for Spt6 in transcription and chromatin structure, we have combined four genome-wide approaches. Our results demonstrate that Spt6 represses transcription initiation at thousand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 104 publications
(186 reference statements)
11
69
0
Order By: Relevance
“…1 and 2). This is in line with the characterization of cryptic promoters in the chaperone mutant spt6-1004 that was published during the review of this manuscript (Doris et al 2018). Our MNase footprint analysis showed that those promoters present a canonical nucleosome array organization and suggested that canonical TFs bind upstream of the iTSSs in the body of genes and are associated to the appearance of intergenic NFR (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…1 and 2). This is in line with the characterization of cryptic promoters in the chaperone mutant spt6-1004 that was published during the review of this manuscript (Doris et al 2018). Our MNase footprint analysis showed that those promoters present a canonical nucleosome array organization and suggested that canonical TFs bind upstream of the iTSSs in the body of genes and are associated to the appearance of intergenic NFR (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, chromatin-sensitive iTSSs can also be detected, albeit at a much lower level, in wild-type conditions (see below). The Winston lab has recently investigated the appearance of intragenic promoters upon Spt6p depletion (spt6-1004) (Doris et al 2018). We compared up to what degree spt6-1004 up regulated intragenic promoters overlap with the chromatin-sensitive cryptic iTSS degined in this study ( Fig.…”
Section: Chromatin-sensitive and Rna Degradationsensitive Cryptic Tramentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, the degron tag described here uses a codon-optimized version of the AID tag and an OsTIR1 gene expressed under the control of the promoter of the yeast GPD1 gene, which ensures reliable and constitutive expression of TIR1 protein (Chan et al, 2018;Eng et al, 2014). Finally, the method is relatively simple and can be adapted to a variety of genomic and proteomic approaches for studying protein function (e.g., Doris et al, 2018;Gopalakrishnan, Marr, Kingston, & Winston, 2019;Shetty et al, 2017).…”
Section: Background Informationmentioning
confidence: 99%